Comparison of natural adsorbent for emulsified wastewater treatment - Mohd Najib, Razali; Aseel, Alhammadi; Musfafikri, Musa; Mohd Khairul Nizam, Mohd Zuhan; Amira Ermafiqka, Anuar (IOP Publishing, 2021)
Oil emulsion is often generated from machining industries, such as computer numerically controlled (CNC) machines and palm oil mill effluent (POME). The current study presents the adsorption strategy in treating the waste emulsion from CNC machines and POME using activated carbon, corncob, and rice husk. To evaluate the adsorbent performance, a jar test apparatus was used with the addition of the adsorbents for treating waste emulsion at the mixing rate of 100 rpm, mixing time of 30 min, and room temperature. The collected wastewater samples were characterised and analysed for chemical oxygen demand (COD), biological oxygen demand (BOD), oil and grease (O&G), and total suspended solids (TSS). Five dosages of activated carbon, corncob, and rice husk were used in the study (i.e., 2, 4, 6, 8, and 10 wt. %) with the control (0 wt. %). The study showed that rice husk and activated carbon managed to reduce pollutants in the emulsified wastewater. Thus, rice husk and activated carbon are suitable for treating industrial waste emulsion.